Constructed wetland for wastewater treatment - Lim, Chu Yan (2024)
The issue of water pollution in Malaysia is getting serious due to urbanization and outdated traditional WWTP and become a great concern of Malaysians. Traditional WWTPs in Malaysia are inefficient at removing interested pollutants such as ammoniacal nitrogen and chemical oxygen demand (COD) since sewage discharge regulations were only enforced after 2009 and are only relevant to new plants built after that year. The study on vertical flow constructed wetlands (VF CW) was conducted to investigate the impact of plant types, substrate types and operation modes on COD removal efficiency. In this research, a total of 5 sets of CW prototypes were built to study the aforementioned interesting parameters: Control, Set A, Set B, Set C and Set D. The duration of the experiment is 21 days and analytical tests were conducted weekly for three weeks. During the experiment period, the prototypes were watered by synthetic wastewater. The plants that were studied in this experiment are vetiver grass (Chrysopogon zizanioides) and spider plants(Chlorophytum comosum), while the substrate types are activated carbon and zeolite. After the experiment, which lasted 21 days, it was concluded that the Set D prototype, which was planted with spider plants and used activated carbon as substrate, had the best performance in COD removal among other prototypes. The average COD removal efficiency of Set D is 77.05 %, with a standard deviation of 13.25 %. Interesting findings were found regarding short contact time but significant COD removal in continuous mode for operation modes. The performance of Set D can also be assessed by nitrogen removal. The nitrification and denitrification efficiency of Set D range from 19.09-126.75 % and 20.83-91.23%, respectively. The outstanding nitrification and denitrification performance of Set D indicates the high potential of CW in COD and nitrogen removal. In short, it is recommended that CW be introduced in conventional WWTP to improve pollutant removal due to its effectiveness and sustainability.